2016
DOI: 10.1016/j.meatsci.2016.02.037
|View full text |Cite
|
Sign up to set email alerts
|

The impact of genetics on retail meat value in Australian lamb

Abstract: Lean (muscle), fat, and bone composition of 1554 lamb carcasses from Maternal, Merino and Terminal sired lambs was measured using computed tomography scanning.Lamb sires were diverse in their range of Australian Sheep Breeding Values for post weaning c-site eye muscle depth (PEMD) and fat depth (PFAT), and post weaning weight (PWWT). Lean value, representing predicted lean weight multiplied by retail value, was determined for lambs at the same carcass weight or the same age. At the same carcass weight, lean va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…Phenotypes for the three traits were all significantly associated with PRICE and, based on the adjusted coefficient of determination (adjusted R 2 ), the multiple linear regression model explained approximately 86.5% of the phenotypic variation in PRICE. As expected, positive economic values were estimated for HCW and AVGCONF, and a negative economic value was estimated FATGR, consistent with the global sheep production goal of increasing lean meat production (Anderson et al., 2016; Tosh & Wilton, 2002). The economic values estimated in this research were greater than the economic values used by Quinton et al (2013), due to the use of updated values in the assumption of the base price per kilogram of HCW and differences in the method in which economic values were estimated.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Phenotypes for the three traits were all significantly associated with PRICE and, based on the adjusted coefficient of determination (adjusted R 2 ), the multiple linear regression model explained approximately 86.5% of the phenotypic variation in PRICE. As expected, positive economic values were estimated for HCW and AVGCONF, and a negative economic value was estimated FATGR, consistent with the global sheep production goal of increasing lean meat production (Anderson et al., 2016; Tosh & Wilton, 2002). The economic values estimated in this research were greater than the economic values used by Quinton et al (2013), due to the use of updated values in the assumption of the base price per kilogram of HCW and differences in the method in which economic values were estimated.…”
Section: Resultssupporting
confidence: 80%
“…The genetic improvement of growth and carcass traits is crucial to increasing the efficiency and profitability of lamb meat production. Consequently, the general objective of most terminal sire sheep breeding programmes is to increase the lean meat production of carcasses (Anderson, Pethick, & Gardner, 2016; Tosh & Wilton, 2002). In recent years, substantial genetic progress for these traits has been made in countries such as Australia (Swan, Banks, Brown, & Chandler, 2017; Swan, Brown, & Banks, 2009; Swan, Pleasants, & Pethick, 2015), New Zealand (Newman, McEwan, & Young, 2009; Sheep Improvement Limited, 2018; Young & Amer, 2009), the United Kingdom (Amer et al, 2007, 2015), Iceland (Eiriksson & Sigurdsson, 2017) and Canada (GenOvis, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Ewe lambs ( n = 125) were sourced from an existing experiment where extensive information on animal genetics was available. Sheep genetics are known to affect lean muscle growth and fat deposition. , Data for dressing percent (%), lean meat yield (%), IMF (%), and shear force (N) were available for the sires of the lambs in the study (data not shown), and these data were used to select low and high IMF genotypes.…”
Section: Methodsmentioning
confidence: 99%
“…Many brassica cultivars (Brassica napus spp. biennis ) and lucerne (alfalfa, Medicago sativa) are nutritious ruminant feeds; however, they are underutilized due to concerns that they can introduce undesirable flavors or taints into meat and other animal products. Although animal genetics is an important determinant of lamb eating quality and flavor, the diet can have direct and indirect effects on meat sensory properties. The energy and protein contents of feeds affect the rate of weight gain, muscle growth, fat deposition, and the underlying meat structure and consequently the textural sensory properties. , Feeds and animal age may also affect the flavor through altering the composition and amount of lipids within the intramuscular fat (IMF); for example, the amount of branched-chain fatty acids (BCFAs) present in ovine fat is associated with “mutton” flavor. ,, Consumers from some Asian backgrounds (e.g., Japanese, Singaporean) are known to be sensitive to BCFAs, which may be a barrier to acceptance of sheepmeat. China is a substantial export market for Australian lamb, and it would be useful to know whether Chinese consumers also have the same sensitivity to BCFAs in lamb. Other compounds derived from rumen metabolism, such as 4-methylphenol ( p -cresol) and 3-methylindole, accumulate in fat reservoirs and are associated with distinct “pastoral” or “barnyard” flavor notes in sheepmeat, which some consumers find undesirable …”
Section: Introductionmentioning
confidence: 99%
“…Lean meat yield, defined as the weight of saleable meat derived from a carcass, is one such factor that is associated with ICDH, iron and myoglobin concentrations Wegner, 2000). Sire breeders in Australia have increased the lean meat yield of lamb carcasses, and hence the potential value of a carcass, through the use of Australian Sheep Breeding Values (ABSVs) (Anderson, Pethick, & Gardner, 2016). The development of breeding values for post-weaning weight (PWT), eye muscle depth (PEMD), and post-weaning c-site fat depth (PFAT) has allowed this selection for lean meat yield.…”
Section: Accepted Manuscriptmentioning
confidence: 99%